Pedagogical challenges in implementing the Merdeka curriculum in English language teaching - Dwi Kurnia Gulo; Trisman Harefa; Riswan Zega; Yaredi Waruwu (Universitas Merdeka Malang, 2025)
This research aims to analyze the difficulties faced by English teachers in implementing the Merdeka curriculum in SMP Negeri 4 Lahewa. The main issue identified is the lack of understanding among teachers regarding the concept of Merdeka curriculum, the limitations of supporting media facilities, and the challenges in implementing flexible teaching methods. The research method used is descriptive qualitative with research subjects consisting of teacher and students in SMP Negeri 4 Lahewa. Data was collected through interviews, questionnaires, and documentation. Data analysis is conducted through the stages of data reduction, data display, and verification or conclusion drawing. Research results show that teachers have a good understanding of the basic principles of the Merdeka curriculum, but teachers face various challenges such as the lack of adequate learning media not fully understanding the mechanism of implementing the Merdeka curriculum causes teachers to still be limited in designing learning modules. In addition, students also face difficulties in adapting to the new learning approaches, especially in terms of communication and self-confidence. The conclusion of this study states that although the Merdeka curriculum has the potential to improve the quality of education, The implementation is still hindered by various obstacles. Therefore, support from the school and government is greatly needed, including more effective training and adequate provision provision. This research provides insights for policymakers in addressing the main challenges faced by teachers when implementing the Merdeka curriculum and improving teachers' personality independently.